Hypoxia-preconditioned mesenchymal stem cells attenuate proinflammatory cytokines in collagen loss animal model - Fristiani, Yeni; Putra, Agung; Sumarawati, Titiek; Setiawan, Eko; Ibrahim, Sugeng; Pramukarso, Dodik Tugasworo Pramukarso (Universa Medicina, 2025)
Background Repeated ultraviolet-B (UVB) exposure induces significant collagen degradation, primarily through overproduction of reactive oxygen species, which subsequently drives an inflammatory cascade. Hypoxia-preconditioned mesenchymal stem cells (H-MSCs) constitute a promising therapeutic approach to counteract collagen loss by modulating inflammatory pathways. This study aimed to evaluate the potential of H-MSCs in regulating NF-κB p65 and IL-1β expression in a collagen loss rat model, highlighting their therapeutic efficacy. Methods Twenty-five healthy male Wistar rats were randomly assigned to five groups: K1 (healthy controls), K2 (collagen loss), K3 (collagen loss + hyaluronic acid), K4 (collagen loss + 2.5 × 10⁵ H-MSCs), and K5 (collagen loss + 5 × 10⁵ H-MSCs). Collagen loss was induced by UVB radiation (peak wavelength: 302 nm) for 2 weeks. mRNA expression of NF-κB p65 was quantified by qRT-PCR, while IL-1β levels were assessed using ELISA. The rats were maintained for 14 days before being sacrificed, to allow the H-MSCs to exert their therapeutic effects. Data analysis was by One-way ANOVA with Tukey’s post-hoc test. Results The administration of H-MSCs significantly reduced IL-1β levels in groups K4 (633.14±63.76 pg/mL) and K5 (520.80±123.82 pg/mL) compared to group K2 (931.93±205.80 pg/mL) (p<0.05), with group K5 showing the most substantial reduction. Moreover, H-MSC injection in groups K4 and K5 effectively reduced NF-κB p65 expression levels (1.13±0.50 a.u. and 0.72±0.22 a.u., respectively), compared to group K2 (2.47±0.50 a.u.) (p<0.05), with group K5 providing optimum inhibition. Conclusion This study demonstrated that H-MSCs effectively attenuate UVB-induced inflammation and modulate key inflammatory pathways.